2015
DOI: 10.1007/s11605-015-2888-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of HER2 Overexpression in Gastric and Gastroesophageal Junction Cancers

Abstract: Rate of HER2 positivity is similar in Turkish patients with GC and GEJCs. HER2 positivity is associated with poor prognosis in patients with early-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
13
2
Order By: Relevance
“…Previous studies showing HER2 amplification or overexpression in 8-54% of GC, especially in intestinal type and distal GC (5). In our recent study, HER2 positivity was 13.7% in Turkish patients (6) Trastuzumab is a humanized monoclonal antibody directed at the HER2 (7). In the trastuzumab for GC (ToGA) trial, trastuzumab-based therapy demonstrated a significant OS benefit in patients with HER2-positive advanced GC (8).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies showing HER2 amplification or overexpression in 8-54% of GC, especially in intestinal type and distal GC (5). In our recent study, HER2 positivity was 13.7% in Turkish patients (6) Trastuzumab is a humanized monoclonal antibody directed at the HER2 (7). In the trastuzumab for GC (ToGA) trial, trastuzumab-based therapy demonstrated a significant OS benefit in patients with HER2-positive advanced GC (8).…”
Section: Introductionmentioning
confidence: 73%
“…The reason of this may be the differences in the study populations, the difference of HER2 expression validated HER2 scoring systems. HER2 positivity was 22.1% of all patients in the ToGA trial, and 13.7% of Turkish patients (6,8). A significant discordance in HER2 status between primary cancer and metastatic sites has been reported in the breast cancer, bladder cancer and prostate cancer (16)(17)(18) The concordance between IHC and fluorescence in situ hybridization (FISH) method is less consistent than that observed in breast cancer (19) In the ToGA trial, the concordance between HER2 positivity detected by IHC and FISH was 87% and the differences were largely due to FISH-positive cases (8).…”
Section: Discussionmentioning
confidence: 95%
“…When the analysis was conducted with intestinal types of cancer, RFS was considerably worse in the HER2-positive group (p=0.011), and Jia et al who proved a significant association between HER2 overexpression, poor clinical outcome, and therapeutic drug resistance [17]. Whereas, Baykara et al [32] found that HER2 positive expression had no significant effect on median OS.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, approximately 7 to 22 percent of esophagogastric cancers overexpress HER-2 [7][8][9]. HER-2 overexpression was positive immunohistocemically in 17.6% of 3264 specimen.…”
Section: The Rationale For Anti-her-2 Therapy In Gastric Cancermentioning
confidence: 97%